COMPOSIÇÃO E DISTRIBUIÇÃO ESPACIAL DA MACROFAUNA BÊNTICA DA PLATAFORMA CONTINENTAL DO MARANHÃO, BRASIL - ROCHA, Lais Rodrigues (2022)
This study presents an evaluation of the composition and spatial distribution of benthic benthic macrofauna which are organisms retained in mesh sizes of 0.5 mm to 5 cm, and associated with the substrate on the Maranhão Continental Shelf. In all, 24 samples obtained 24 samples distributed in three transects during the rainy period of April 2019, aboard the ship Ciências do Mar II. The environmental characterization suggests an environment with homogeneous spatial variation as predominantly sand, high hydrodynamics, low concentration of organic matter, high temperature (>21.9 °C) high salinity (>17 g kg -1 ), well oxygenated (>6.2 mg L -1 ), and with the influence of three water bodies: river water, coastal water and tropical water. The relative abundance of benthic macrofauna was 201,288 organisms, distributed in six taxonomic taxonomic groups. Among the main groups, Gastropoda exhibited the highest abundance (59%), followed by Bivalvia (30%). The ecological indices indicate an environment with low richness (S<5) and diversity (H'<1), with heterogeneous distribution of the major groups, represented by low equitability (J'<0.5) and high dominance (Do>0.5). As for the influence of environmental parameters on benthic macrofauna it is possible to observe a higher abundance of Bivalvia associated with the parameters sand, temperature and dissolved dissolved oxygen, and of Gastropoda associated with suspended particulate matter organic matter, gravel and depth.